Efficacy and Safety of Low-Dose Lenvatinib and Toripalimab in Patients With Recurrent Platinum-Resistant Ovarian Cancer: Study Protocol of a Multicenter, Open-Label, Single-Arm, Phase II Clinical Trial - Su H; Shang X; Liu H; Wang Y; Yu Y; Xu Y; Jiang K; Feng F (International Journal of Women's Health)
Hao Su,1,* Xiao Shang,1,* Hongruo Liu,2 Yutong Wang,1 Yang Yu,3 Yanhua Xu,4 Kui Jiang,2,* Fengzhi Feng1,* 1Department of Obstetrics and Gynecology, National Clinical Research Center for Obstetric & Gynecologic Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Medical Oncology, The Second Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, People’s Republic of China; 3Department of Obstetrics and Gynecology, Xing’an League People’s Hospital, Xing’an League, Inner Mongolia, People’s Republic of China; 4Department of Obstetrics and Gynecology, Jinan Maternity and Child Health Care Hospital, Jinan, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fengzhi Feng, Department of Obstetrics and Gynecology, National Clinical Research Center for Obstetric & Gynecologic Diseases, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, No. 1 Shuai Fu Yuan, Dong Cheng District, Beijing, 100730, People’s Republic of China, Email fengfz1969@sina.com Kui Jiang, Department of Medical Oncology, The Second Affiliated Hospital of Dalian Medical University, Dalian, Liaoning, 116023, People’s Republic of China, Email jk0411@163.comPurpose: Therapeutic options for patients with platinum-resistant ovarian cancer (PROC) remain a major unmet need. PROC patients with multiple recurrences are unable to continue highly toxic treatment after prior multiple lines of systemic therapy. Chemotherapy-free option lenvatinib plus anti-programmed cell death protein-1 (PD-1) combination therapy has shown promising results in several malignancies including ovarian cancer, but the toxicity of a high starting dose of lenvatinib is also notable and needs to be improved. Our previous pilot study indicated that a reduced starting dose of lenvatinib may maintain comparable anti-tumor activity with favorable safety in heavily pre-treated ovarian cancer. This study is designed to further validate the efficacy and safety of the combination therapy of low-dose lenvatinib and PD-1 inhibitor toripalimab in patients with recurrent PROC.Study Design and Methods: The study is designed as a multicenter, open-label, single-arm, prospective phase II study. Patients with recurrent epithelial ovarian cancer who have disease progression either during or within 6 months after completion of platinum-based therapy will be included. A total of 69 participants will receive low-dose lenvatinib (8 mg or 12 mg, daily, orally, based on patient’s body weight) and toripalimab (240 mg, every 21 days, intravenously). Treatment will continue until the development of unacceptable toxicity or disease progression. The primary endpoint is the progression-free survival. The secondary endpoints include objective response rate, duration of response, disease control rate, overall survival, toxicity and patients’ quality of life. Exploratory objectives aim to identify biomarkers and molecular signatures for predicting response or prognosis.Keywords: ovarian cancer, platinum-resistant, immune checkpoint inhibitor, lenvatinib, dose adjustment